Optimasi Waktu Pelaksanaan Pembangunan Ruang Praktik Siswa SMK Negeri 1 Duduksampeyan dengan Metode PERT - Bowo Leksono; Dandy Nugroho; Eva Indah Yanti (Wahana Teknik, 2020)
Implementation of work on a project requires not only reliable human resources, but also a good management. A construction project can be said to be successful if it is able to meet its objectives that is completed at the specified time, in accordance with the allocated costs and meet the required quality. Or failure of the implementation is often caused by lack of planned project is not effective and efficient, this will cause delays, lack of quality work, and too large funding is not in accordance with initial planning. In this paper the author uses planning techniques with network planning as one of the models that will be used in the implementation of the student practice room development project at SMK Negeri 1 Duduksampeyan. The planning technique used by the author is PERT. This technique is used to optimize the construction project construction where the author examines issues related to time. By comparing the actual situation and the plan, it can be seen whether the progress of the relevant project is on schedule or delayed. From the research that has been done, it is obtained using a time schedule. Based on the analysis using the PERT method the result is the opportunity to achieve the target time for completion of the project from 90 days to 72 days is 99.75% and the project cost increased to Rp 423,380,476.82 from the original planned cost of Rp 422,066,726.74. There was a reduction in project time for 18 days and an increase in costs of Rp 1,313,750.08. Keywords: network, optimation, PERT, planning.